Metropolis - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2019)
Summer, 1928. Berlin, a city where nothing is verboten. In the night streets, political gangs wander, looking for fights. Daylight reveals a beleaguered populace barely recovering from the postwar inflation, often jobless, reeling from the reparations imposed by the victors. At central police HQ, the Murder Commission has its hands full. A killer is on the loose and though he scatters many clues, each is a dead end. It's almost as if he is taunting the cops. Meanwhile, the press is having a field day. This is what Bernie Gunther finds on his first day with the Murder Commisson. He's been taken on beacuse the people at the top have noticed him--they think he has the makings of a first-rate detective. But not just yet. Right now, he has to listen and learn.